A Public Juridic Person in Canon Law Seeking Chapter 11 Bankruptcy Protection in the United States: Theory, Process, and Application - Pham, Bryan V. (Université Saint-Paul / Saint Paul University, 2016)
According to the 1983 Code of Canon Law, public juridic persons in the Catholic Church are erected by competent ecclesiastical authority. Endowed with the right to acquire, retain, administer, and alienate ecclesiastical goods (i.e., properties), public juridic persons receive their mission from the Church, speak in the name of the Church, and make available their ecclesiastical goods to further the mission of the Church. In the United States of America, administrators of public juridic persons generally have the option to be incorporated under civil law. When civilly incorporated, these institutions are afforded the same legal rights and protections that other corporations have under civil law. The right to file for reorganization bankruptcy under Chapter 11 of Title 11 of the federal Bankruptcy Code of the United States is among those rights. This dissertation proposes that civilly incorporated public juridic persons should file for reorganization bankruptcy under Chapter 11 of the Bankruptcy Code when faced with insurmountable pressures from claimants and creditors and when their stable patrimonial condition is at risk. To achieve this objective, this dissertation begins by providing a survey understanding of public juridic persons (chapter one) and the care of their ecclesiastical goods (chapter two) according to the CIC/83. Next, this dissertation surveys the nature and the process of reorganization bankruptcy under Chapter 11 of the Bankruptcy Code (chapter three). Finally, in light of the technical principles and the theories developed in the previous chapters, this dissertation proposes a method for civilly incorporated public juridic persons to file for reorganization bankruptcy under Chapter 11 (chapter four).
Keywords: canon law; temporal goods; ecclesiastical goods; chapter 11; bankruptcy; juridic person; public juridic person; religious institutes; parishes; dioceses; United States; federal law